Chronic vulvovaginal candidiasis: characteristics of women with Candida albicans, C glabrata and no candida. Issue 5 (October 1995) - Geiger, A M; Foxman, B; Sobel, J D
Abstract : INTRODUCTION--Although as many as 5% of all women complain of chronic vulvovaginitis, little is known about these women. They may often be misdiagnosed and the role of vaginal yeast culture in diagnosing vulvovaginal candidiasis (VVC) among them has not been clearly defined. METHODS--To address these deficiencies, we tabulated initial diagnoses among new patients and conducted a medical record-based, unmatched case-control study among women reporting a history of chronic vulvovaginitis (four or more episodes in the past year) at a vulvovaginitis specialty clinic. Clinical presentation and medical history were compared for women who had a positive vaginal yeast culture for either Candida albicans or C glabrata, or who had a negative culture. RESULTS--One-third of the women had no apparent vulvovaginal disease at their initial visit. All women reported similar symptoms, except for an increased prevalence of painful sexual intercourse in women with C albicans (chi 2 p = 0.014 versus women with C glabrata and p < 0.001 versus women with no candida). Women with C glabrata were more likely to be non-white (chi 2 p = 0.071 compared with women with C albicans) and to report an underlying medical condition (chi 2 p < or = 0.001 versus both women with C albicans and women with no candida). Physical examination was normal only in women with no candida. C albicans cases were more likely to have positive potassium hydroxide microscopy (chi 2 p = 0.016) and a pH < or = 4.5 (chi 2 p = 0.011) than were C glabrata cases. CONCLUSIONS--These results suggest that reliance on symptoms and signs alone will result in significant misdiagnosis of chronic vulvovaginitis. Among women with VVC, subtle differences in clinical presentation do not reliably distinguish women with C albicans from those with C glabrata. Our study also indicates that vaginal yeast cultures, while not necessary for every patient, are valuable in confirming negative diagnoses, detecting microscopy false-negatives, and identifying non-C albicans isolates.